Using the EAMENA database to document modern heritage: the Amman Heritage Houses, Jordan, case study. (2nd September 2021) - Mubaideen, Shatha; Salameen, Dana; Momani, Rudaina Al
Abstract : This paper assesses and discusses the potential of using the EAMENA database for documenting tangible heritage in Jordan post-1750 CE, for example, Ottoman and 20th-century heritage sites and architecture. Representing an example of the important process of feedback and knowledge-exchange that has characterized the development of the EAMENA database, this research addresses how practical the EAMENA database is for documenting the recent heritage of Jordan in its current form and how it could be adapted to be more suitable. The paper uses the case study of the Amman Heritage Houses (AHH) documentation project to explore possibilities for new efforts or solutions, and to identify key recommendations and strategies for the future development of the database. The findings aim to fortify the strengths and mitigate the weaknesses when using the database for post-1750 CE heritage in decision making by heritage professionals and planners.